The effect of learner-generated digital materials on learners’ deep learning approach and self-efficacy - Alwafi, Enas Mohammad (Journal of Education and e-Learning Research, 2023)
This study aimed to explore the effect of learner-generated digital materials on students’ deep learning approach and self-efficacy. A quasi-experimental design that involves a pre-test, a post-test, a control group and an experiment group was used in this study which involved 51 students (25 students participated in the control group and 26 students participated in the experiment group). A questionnaire was used to measure students’ deep learning approach and self-efficacy. The study found that students in the experimental group improved their deep learning approach and self-efficacy more than students in the control group. Learner-generated digital materials can enhance students’ learning experiences. This study contributes new knowledge about the methods by which learner-generated digital material can be used as a learning approach. It also provides insight on how digital tools can be used to support students learning. This study provides recommendations for employing learner-generated digital materials to engage students in the learning experience.